PENILAIAN PROGRAM PRAKTIKUM TERHADAP PENINGKATAN KUALITI GURU PRA PERKHIDMATAN: ANALISIS BERDASARKAN LATENT GROWTH CURVE MODELLING - Sarkowi, Azizah; Ishak, Mohd Sobhi (Journal of Techno-Social, 2015)
Practicum is an important component in teacher education programs. This study identify the improvement in the quality of pre-service teachers for three phases practicum. Multi-point prospective panel study has been conducted on a 541 pre-service teachers at the Institute of Teacher Education. Teacher’s quality is measured based on the achievement of program learning outcomes. Based on matching last six digit identification card number for three studies series, 337 questionnaires were analyzed using a latent growth curve model using AMOS 18.0. Latent Analysis shows that the model achieve goodness of fit. There is a linear trend of improvement in the performance of the three phases of the practicum. This increase varies between individuals and the rate of growth depends on the level of achievement at practicum phase I. Studies indicate that the increase in the practicum period of teacher education policy should be continued.